Thermal analysis of conjugated cooling configurations using phase change material and liquid cooling techniques for a battery module - Song, Limin (2021)
A novel conjugated cooling configuration using phase change material (PCM) and liquid cooling techniques is proposed, and its thermal performance is investigated for a battery module. 106 cylindrical batteries are connected to the cold plate at the bottom through a heat spreading plate and the adjacent thermal columns, with PCM filled in between the gaps, which forms the cooling configuration. Three-dimensional numerical models are established for the cooling of the representative battery and battery module, which includes the battery connected to a liquid cooled mini-channel cold plate through the heat spreading plate and thermal column structures. The thermal characteristics of the battery incorporating the PCM melting and liquid cooling are examined at large flow rate. The geometrical parameters such as the size of the thermal column, the thickness of the heat spreading plate and the spacing of the batteries are investigated for the present conjugated cooling configuration. Both the battery temperature ramp-up rate and the steady-state battery temperature are significantly reduced by the conjugated cooling, in comparison with single PCM or liquid cooling conditions. The effects of various structure parameters on the thermal performance can be visualized by plotting the working time t50 vs the heat density based on the PCM volume. A comparison of the numerical simulation with the preliminary experiment work shows good agreement. This work can be useful in the design of conjugated configurations for the battery thermal management.